Pemanfaatan Maggot Sebagai Media Pengurai Sampah Organik - Rachmanto, Deny; Aufa, Hikari; Maulana, Muhammad Arfan; Aviani, Rachma; Pertiwi, Suci Diah; Rozy, Fahrur; Burhan, Muhamad Shohibul; Maharani, Rara Eva; Wardhani, Adjie Kesuma; Sunardi, Sunardi (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The organic waste problem in RW 08 Warungboto has become a pressing environmental issue, marked by a continuously increasing volume and suboptimal management. This Community Service Program aims to address this issue through the socialization of maggot (Black Soldier Fly larva) utilization as an organic waste decomposition medium. The methods used include designing maggot cage tailored to local conditions and needs, interactive socialization with practitioners from the Jogja Maggot Cage Community covering the benefits of maggots, simple cultivation techniques, and the utilization of by-products (kasgot) as fish feed, interactive discussions, and activity evaluation. The output of this socialization is an increased awareness and interest in maggot cultivation as an organic waste management solution, as well as an understanding of the utilization of kasgot as valuable fish feed. Additionally, the resulting maggot cage design provides a practical guide for the community to independently build maggot cages, thereby facilitating the implementation of maggot cultivation at the household level. This program is expected to encourage the widespread application of maggot cultivation in RW 08 Warungboto, thus contributing to better organic waste management and a healthier environment. Furthermore, it is expected to create a collective awareness within the community about the importance of sustainable waste management. Beyond ecological benefits, this program also provides opportunities for the community to develop maggot-based small and medium enterprises, which can become a source of additional income. The successful implementation in RW 08 Warungboto is expected to serve as a model that can be adopted by other communities, expanding its positive impact in improving the quality of life and economic resilience of the community